Optimalisasi Peran Pemerintah Melalui Badan Bank Tanah Sebagai Land Manager Negara Dalam Pengelolaan Penyediaan Tanah Bagi Kepentingan Pembangunan: Optimising The Government Role Through Indonesia Land Bank Authority As The State Land Manager In Managing Land Provision For Development - Himawan Arief Sugoto; M. Syamsul Maarif; Budi Mulyanto; Harianto (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
The limited availability of land and the high price of land make it difficult for the government to carry out sectoral development. To overcome this problem, the government has established a special agency (sui generis) in 2021, the Indonesia Land Bank Authority. The purpose of this study is to conduct a study of the regulations and legal entities that manage the provision of land using the Regulatory Impact Assessment (RIA) research method. The scope of the study is limited to regulations and institutions related to land provision management, namely Perumnas, BP Batam, Land Bank Agency and Private Enterprises. The results show the limited role of the Ministry of ATR/BPN and the suboptimal role of various forms of institutions as state land managers in managing land supply, especially in relation to overlapping land acquisition functions in existing agencies. In conclusion, this research proposes a policy that the only appropriate institution as the State Land Manager is the Land Bank Agency due to its specificity (sui generis), which can flexibly carry out public and private interests in land supply management. However, in its implementation, this agency needs regulatory support to effectively become the state land manager, namely through a one-door policy for the government's land acquisition function. Keywords: state land manager, Indonesia land bank authority, ria, public and private interest, land provision management